Is fin-tech the new panacea for poverty alleviation and local development? Contesting Suri and Jack's M-Pesa findings published in Science. Issue 161 (3rd July 2019) - Bateman, Milford; Duvendack, Maren; Loubere, Nicholas
SUMMARY: Financial technology, or simply 'fin-tech', is increasingly seen as one of the key tools to facilitate poverty reduction and local economic development. One article in particular by Tavneet Suri and William Jack published in the leading publication Science has played a hugely influential role in promoting the fin-tech model in the global South using the example of Kenya's iconic M-Pesa money transfer platform. The authors' central claim is that M-Pesa has been instrumental in facilitating a major episode of poverty reduction. Our analysis shows that their analysis and claims are extremely problematic.